Whey Peptide–Based Formulas With ω‐3 Fatty Acids Are Protective in Lipopolysaccharide‐Mediated Sepsis. (3rd February 2014) - Tsutsumi, Rie; Horikawa, Yousuke T.; Kume, Katsuyoshi; Tanaka, Katsuya; Kasai, Asuka; Kadota, Takako; Tsutsumi, Yasuo M.
Abstract : Background: Sepsis and septic shock syndrome are among the leading causes of death in critically ill patients. Lipopolysaccharide (LPS) released by bacteria within the colon may translocate across a compromised epithelium, leading to oxidative stress, inflammation, sepsis, and eventually death. Methods : We examined the effects of a whey‐based enteral formula high in cysteine (antioxidant precursor) and the addition of ω‐3 fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), against a mouse model of LPS‐induced sepsis. Mice were fed either a whey‐based diet with EPA‐DHA (PAF), a whey‐based diet without EPA‐DHA (PSTD), or a casein‐based control diet (CONT). Results : Mice fed PAF or PSTD were protected against LPS‐induced weight loss. Whey‐based diets suppressed inflammatory cytokine release and oxidative stress damage. Furthermore, PAF and PSTD were able to inhibit autophagy, a mechanism in which the cell recycles damaged organelles. These anti‐inflammatory and antioxidative effects of PSTD and PAF resulted in decreased liver inflammation and intestinal damage and promoted protective microbiota within the intestines. Conclusions : These data suggest a clinical role for whey peptide–based diets in promoting healing and recovery in critically ill patients.